Antioxidative status as assessed by enzymatic activity in the tear fluid and by the levels of sulfur-containing protein groups in the blood and tear fluid of myopes before and after treatment with a thiol agent (Ukrainian Journal of Ophthalmology, 2026)
Background: Myopia remains a leading cause of vision loss and visual disability in Ukraine (75%) and one of the most common ocular disorders worldwide. Most of available biological materials like blood and tear fluid can be used to measure the levels of these compounds, and thus to assess the relative balance between lipid peroxidation (LPO) and antioxidant system (AOS) in myopes. This will enable to find a pharmacological way for normalizing this balance in order to prevent degenerative retinal changes, and to stop the progression of myopia.Purpose: To evaluate the antioxidant status in patients with different severity of myopia based on the activity of enzymes (glutathione-S-transferase (GST), catalase (CAT), and glutathione peroxidase (GPx)) in their tear fluid and of sulfur-containing protein groups in their blood and tear fluid before and after treatment with Fakovit, a thiol agent.Materials and Methods: The Facovit treatment group included 67 myopes (low myopes, n = 26; medium myopes, n = 22; high myopes, n = 19) aged 12-24 years, whereas the control group included 67 aged-matched who did not receive Facovit treatment. In addition, 30 aged-matched healthy individuals were included into the study.Results: At baseline, GPx neutralized lipid hydroperoxides too slowly, and GST activity was markedly inhibited, with GST activity in the tear fluid and in the blood in low, moderate and high myopes of the Fakovit treatment group being statistically significantly lower than in normal individuals. In addition, CAT activity in the tear fluid in moderate and high myopes of this group was low. The baseline levels of free and protein-bound sulphydryl and disulphide groups in the tear fluid in low, moderate and high myopes of the Fakovit treatment group were abnormal, indicating substantial abnormalities of the AOS, with the tear fluid levels of free sulfhydryl groups and of protein-bound sulfhydryl groups being statistically significantly lower, and with the tear fluid levels of free disulphide groups and of protein-bound disulphide groups being higher than in normal individuals. Biochemical study demonstrated that the treatment including the thiol agent resulted in a substantial increase in the activity of enzymes (GPx and GST) of the detoxification system.Consclusion: Fakovit was found to have a substantial antioxidation effect on thiols in myopia, with increase in the levels of free sulfhydryl groups and decrease in the levels of protein-bound disulphide groups in the blood and tear fluid.
Keywords: myopia; antioxidation system; enzymatic activity in the tear; level of sulfur-containing protein groups in blood and tear fluid; Fakovit; a tiol agent